Implementasi kebijakan pengelolaan jaringan dokumentasi informasi hukum di Sekretariat Jenderal MPR RI Tahun 2018-2022 - Sari, Dian Kartika; Widjayanti, Arifiani; Karunia, R. Luki (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
The Legal Documentation and Information Network (JDIH) Management Policy is a form of public services using ICT inÂ providing legal data and information sources which can be easily, briefly, clearly and completely accessed by public The Secretariat General of the MPR RI as a supporting system for the Assembly is one of the members of the National JDIH. However, since was formed in 2018 until 2022 it has not been able to implement this policy properly. The management of JDIH that has not been well organized, the overlapping functions between the website management unit and the JDIH implementation team, infrastructure facilities that are not optimal, insufficient number and competency of human resources are some indicators as the weakness of JDIH implementation of MPR. This article will discuss about the implementation of JDIH management policy at the Setjen MPR RI, why is it still not running as expected and recommend some strategic steps to improve the JDIH in the future. This research uses study case qualitative methods with the Edward III and Grindle models as analytical tools. Data collection carried out using in-depth interviews, observation and documentation.